The Asian turn in foreign investment / edited by Mahdev Mohan, Chester Brown. - Mohan, Mahdev; Brown, Chester, 1972- (Cambridge University Press, 2021)
This collection critically discusses the increasing significance of Asian States in the field of international investment law and policy. Consisting of contributions authored by a leading team of scholars and practitioners of international investment law, this volume contains analyses of both national and multilateral investment law rule-making in Asia, including a critical discussion of certain States' approaches to balancing the different tension between investment protection and the preservation of States' regulatory sovereignty. It also contains thematic chapters on cutting-edge developments which are of relevance to Asia as well as the global community, such as investors' obligations of due diligence, additional transparency in treaty-based investment arbitration responses by ASEAN member States to transboundary haze pollution, and the relevance of human rights obligations in international investment law. It also contemplates future possibilities for investor-State dispute settlement, including the use of investor-State mediation in view of the Singapore Convention on Mediation.